The Construction of sexuality on social media in China : a semiotic analysis of Durex condom advertisements - Wu, Juanhui (2019)
This thesis presents a semiotic analysis of the construction of sexuality in condom advertisements, in particular, it investigates the phenomenon of how Durex constructs sexuality on social media in China. The purpose of the study is to decode sexuality on Chinese social media from Durex’s advertisements. It aims to show how Durex constructs sexuality and applies Chinese culture on social media posts. The analysis is adopted through semiotic theories. This thesis applies Pierce’s, Roland Barthes, and Chandler’s model of semiotic analysis to decode data. Through a semiotic approach, it defines the mode of signs, interprets the meanings, identifies image rhetoric and analyses relationships between verbal and visual signs. To this end, six advertisements are selected from Durex’s Chinese social media platform – Weibo. The selected advertisements are related to traditional Chinese festivals or important days in Chinese culture. The findings show that sexuality on Chinese social media is communicated through witty implicitness, heteronormative idealization, cultural continuity and appreciation from Durex’s advertisements. Durex builds rapport through creating a celebrative or humorous atmosphere, wordplay, word replacement, and ambiguity connoted by references to traditional culture.